The finances of pastoral visits. Considerations based on the examples of Florence and Lucca (Studi di storia medioevale e di diplomatica - Nuova Serie, 2025)
The essay employs an economic perspective to explore the late medieval pastoral visits. This practice was not only an act of episcopal governance, but also a matter of financial administration, as it generated significant revenues for the bishops and entailed costs for the visited, thus falling under the jurisdiction of diocesan taxation. These revenues were not merely ancillary to other assets; rather, they serve to underscore the profound interconnection between episcopal power and economic resources.
Keywords: Tuscany; Late Middle Ages; Money; Pastoral visits